2020
DOI: 10.1021/acs.chemmater.0c02588
|View full text |Cite
|
Sign up to set email alerts
|

Area-Selective Deposition of Ruthenium by Area-Dependent Surface Diffusion

Abstract: Area-selective deposition (ASD) enables the growth of materials on target regions of patterned substrates for applications in fields ranging from microelectronics to catalysis. Selectivity is often achieved through surface modifications aimed at suppressing or promoting the adsorption of precursor molecules. Here, we show instead that varying the surface composition can enable ASD by affecting surface diffusion rather than adsorption. Ru deposition from (carbonyl)-(alkylcyclohexadienyl)Ru and H 2 produces smoo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
68
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 46 publications
(70 citation statements)
references
References 87 publications
2
68
0
Order By: Relevance
“…It is considered that ASD is mainly originated from competition between surface chemisorption, decomposition and so on [33]. To elucidate the origin of selective growth, the density functional theory (DFT) and nudged elastic band (NEB) are adopted to calculate the decomposition energy and energy barriers of ALD precursors on Pt, Cu and SiO 2 surfaces, as shown in Figure 5a.…”
Section: The Origin Of Selective Growthmentioning
confidence: 99%
“…It is considered that ASD is mainly originated from competition between surface chemisorption, decomposition and so on [33]. To elucidate the origin of selective growth, the density functional theory (DFT) and nudged elastic band (NEB) are adopted to calculate the decomposition energy and energy barriers of ALD precursors on Pt, Cu and SiO 2 surfaces, as shown in Figure 5a.…”
Section: The Origin Of Selective Growthmentioning
confidence: 99%
“…[6,24] The impact of surface diffusion and aggregation was recently also demonstrated for Ru ASD by (carbonyl)(cyclohexadienyl)Ru/H 2 CVD at a much lower deposition temperature of 250 °C, driven by high surface energy of Ru and the low surface energy of the methyl-terminated SiO 2 nongrowth surface. [12] The experimental-theoretical study indicated an average diffusion length of 140 nm for Ru adspecies on the methyl-terminated SiO 2 nongrowth substrate. Indeed, diffusionmediated Ru ASD was observed in SiO 2 -TiN line-space patterns with a critical dimension of 45 nm and SiO 2 line height of 60 nm.…”
Section: Introductionmentioning
confidence: 98%
“…[7][8][9] The roles of gas phase and surface diffusion have long been known in selective epitaxial growth by CVD. [6,7,[10][11][12][13][14][15][16][17][18][19][20] The resulting fluxes reduce deposition on the nongrowth surface and enhance the growth rate on the growth surface. As a consequence, the growth rate and selectivity depend on the pattern dimensions and geometry when the pattern dimensions are comparable or smaller than the characteristic diffusion length.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations